Study of Policy Coherence in Coastal Community Development Based on Local Wisdom in Coastal Urban Area - Tjitjik Rahaju; Bondan Wijanarko; Meirinawati (The Journal of Indonesia Sustainable Development Planning, 2025)
Policy plays a vital role in addressing the complex economic, social, and environmental challenges faced by coastal communities. This study examines the degree of coherence among coastal community development policies in Surabaya City, focusing on alignment between cross-sectoral policies and local wisdom–based community empowerment programs in the eastern coastal area. Community empowerment is assessed through policy implementation actors, program managerial aspects, and program targets, using parameters such as increased access and market share, expanded access to capital, and improved capacity to manage capital through cooperatives. Methodologically, the study applies MACTOR to analyze actor dynamics and spatial analysis to map the distribution and proximity of empowerment programs. Findings indicate that existing policies show limited coherence, especially in cross-sectoral integration and program synergy. Although community groups serve as key drivers, institutional fragmentation constrains policy effectiveness. Stronger policy alignment and multi-actor coordination are therefore essential to improve coastal community welfare and sustainability.